KERAGAMAN ORIENTASI PENDIDIKAN DI PESANTREN - Husen Hasan Basri (Jurnal Dialog, 2014)
Pesantren (Islamic boarding schools) have been experiencing a rapid growth both quantitatively and qualitatively; shown by the increasing numbers of pesantren and their santri (students) as well as by the various educational orientations. This paper explores how pesantren viewed and articulated the education that they conducted. It applies literature study on several pesantrens which were previously investigated by the Research and Development Centre of Religious Education/Religiousity, other institutions, and individuals for the last 10 years. Additionally, it points out that the diversity of pesantren’s educational orientation was by and large influenced by the ideology of their leaders and managers. A variety of salafiyah (traditional) pesantrens showed a phenomenon of educational dynamicity. As for the variants of modern Gontor pesantren and its networking, education reformation has been the main issue as coined by their founders. Some other pesanten that had relations to modern Gontor pesantren, such as al-Mukmin Ngruki, al-Zaitun, and Hidayatullah focused on preparing Muslim cadres. Moreover, the variants of salafi pesantren constructed their education orientation to maintain the continuity of salafi cultures.